Embracing the "New Normal": exploring readiness among Filipino students to engage in virtual classes. (2nd January 2022) - Collado, Zaldy C.; Landagan, Myra D.; Villareal, Mark Godwin B.; Rescober, Angeli Ann S.; Baral, Grace D.; Pantaleta, Floraime O.; Banaria, Dionimar B.; Cortez, Carlo P.
ABSTRACT: This paper is an examination of learner readiness to engage in non-traditional modes of schooling, such as online or distance learning, in which the overall interest lies in ensuring the access of Filipino students to quality education even during this pandemic. The specific goal is to gauge and investigate material, psychological, and home environment readiness among incoming and incumbent college students in the Philippines. The findings were drawn from 512 survey respondents whose answers were collected online. Among others, results reveal that majority of our respondents own computer devices and have access to the internet but are not confident about the service integrity of their internet connection. Most respondents also expressed that virtual classes are less motivating due to absence of physical connection to teachers and schoolmates, which could negatively impact the learning experience. They also voiced out reservations on the conduciveness of their home environment for online learning. We argue that it is only through paying attention to learner readiness that decision-makers can safeguard education as an accessible right to all.